An experimental and analytical research on moment redistribution in reinforced concrete continuous beams - Aydogan, Mehmet Safa; Aydemir, Cem; Arslan, Guray (TAYLOR & FRANCIS LTD, 2024)
This paper consists of the results of experimental and analytical studies carried out to determine the moment redistribution in reinforced concrete (RC) continuous beams realistically, which are frequently used structural forms in buildings. It was determined that the parameter affecting the moment redistribution the most was the reinforcement ratio, so six RC continuous beams were produced with different reinforcement ratios. In this study, the tensile reinforcement ratio (& rho;), the compressive reinforcement ratio (& rho;'), and the balanced reinforcement ratio (& rho;(b)) in the intermediate support sections are considered as the main variables, and the effects of two parameters on the moment redistribution capacities of the beams are investigated. While one of them is (& rho;'/& rho;), the other one is (& rho;/& rho;(b)). Considering the experimental results obtained, a simple formulation has been proposed by taking into account the neutral axis depth factor (c/d), which is the parameter frequently used in the determination of moment redistribution in the literature and in the design code provisions. Moreover, a database was created by considering the experimental results of 80 beams collected from the literature and it was aimed to determine the effectiveness of this proposed formulation compared to the equations in the literature and in the design code provisions. According to the results, it was determined that the proposed formulation gave better statistical outcomes than the others. It is thought that the design codes statistically give more negative results than the results of this study, as they generally prefer to be on the safe side deliberately. In addition to moment redistribution, the general behaviors of RC continuous beams under concentrated loads, such as load-displacement relationships, ductility, energy dissipation, and moment-curvature relationships have also been investigated in detail.
Keywords: Moment redistribution; analytical study; continuous beams; plastic rotation capacity; ductility; curvature; CURVATURE DUCTILITY; RC BEAMS; STRENGTH; PERFORMANCE; Engineering